Development of Transport Properties Characterization Capabilities for Thermoelectric Materials and Modules. Issue 1774 (2015) - Reyes-Gil, Karla R.; Whaley, Josh; Nishimoto, Ryan; Yang, Nancy
ABSTRACT: Thermoelectric (TE) generators have very important applications, such as emerging automotive waste heat recovery and cooling applications. However, reliable transport properties characterization techniques are needed in order to scale-up module production and thermoelectric generator design. DOE round-robin testing found that literature values for figure of merit (ZT) are sometimes not reproducible in part for the lack of standardization of transport properties measurements. In Sandia National Laboratories (SNL), we have been optimizing transport properties measurements techniques of TE materials and modules. We have been using commercial and custom-built instruments to analyze the performance of TE materials and modules. We developed a reliable procedure to measure thermal conductivity, seebeck coefficient and resistivity of TE materials to calculate the ZT as function of temperature. We use NIST standards to validate our procedures and measure multiple samples of each specific material to establish consistency. Using these developed thermoelectric capabilities, we studied transport properties of Bi2 Te3 based alloys thermal aged up to 2 years. Parallel with analytical and microscopy studies, we correlated transport properties changes with chemical changes. Also, we have developed a resistance mapping setup to measure the contact resistance of Au contacts on TE materials and TE modules as a whole in a non-destructive way. The development of novel but reliable characterization techniques has been fundamental to better understand TE materials as function of aging time, temperature and environmental conditions.